2008
DOI: 10.1111/j.1748-0361.2008.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Research on Rural Veterans: An Analysis of the Literature

Abstract: The literature on rural veterans' health care needs warrants expansion and investment so that policy makers can make informed decisions in an environment of limited resources and competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 65 publications
1
63
0
Order By: Relevance
“…For example, one potential explanation for the relatively low rates of screening among disadvantaged White veterans is that these individuals are more likely to live in rural areas than their Black counterparts and therefore may have more difficulty accessing VA care. 70,71 Also, the dominant modes of CRC screening differ within and outside the VA. FOBT is the dominant mode of screening within the VA whereas screening by colonoscopy is more common outside the VA. We conducted additional analyses and found that, among those who were adherent to CRCS, Black veterans had significantly higher rates of FOBT (60% vs. 53%, p=0.025) and lower rates of colonoscopy compared with White veterans (47% vs. 57%, p = 0.012). It may be the case that higher SES Black veterans, who are more likely than their lower SES Black counterparts to receive care outside the VA, are less likely to be offered a colonoscopy than whites receiving care outside the VA. Alternatively, higher SES blacks may be less likely than their white counterparts to find the option of colonoscopy acceptable (perhaps because it is an invasive procedure or because they are more likely to be unmarried and hence lack the necessary support required for the procedure).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one potential explanation for the relatively low rates of screening among disadvantaged White veterans is that these individuals are more likely to live in rural areas than their Black counterparts and therefore may have more difficulty accessing VA care. 70,71 Also, the dominant modes of CRC screening differ within and outside the VA. FOBT is the dominant mode of screening within the VA whereas screening by colonoscopy is more common outside the VA. We conducted additional analyses and found that, among those who were adherent to CRCS, Black veterans had significantly higher rates of FOBT (60% vs. 53%, p=0.025) and lower rates of colonoscopy compared with White veterans (47% vs. 57%, p = 0.012). It may be the case that higher SES Black veterans, who are more likely than their lower SES Black counterparts to receive care outside the VA, are less likely to be offered a colonoscopy than whites receiving care outside the VA. Alternatively, higher SES blacks may be less likely than their white counterparts to find the option of colonoscopy acceptable (perhaps because it is an invasive procedure or because they are more likely to be unmarried and hence lack the necessary support required for the procedure).…”
Section: Discussionmentioning
confidence: 99%
“…If it is the case that living in a rural setting accounts for low rates of CRCS among disadvantaged White veterans, it will be critical to develop strategies to improve screening in this population. 70,71 Additional research is also needed to understand why Black veterans are less likely to be screened by colonoscopy than their White counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that 20% of veterans live more than 50 miles from the nearest VA medical [31,32,35]. Moreover, other studies have documented poorer care among rural veterans for acute myocardial infarction, another emergent condition [1,2,26].…”
Section: Discussionmentioning
confidence: 73%
“…Mean length of stay among female Veterans was significantly longer for VA hospitals than private-sector hospitals even after adjustment for patient differences (Mooney & Weeks, 2007). Weeks et al (2008a) identified Veteran stays in VA and non-VA hospitals and found longer length of stay for VA hospitalization even after adjusting for patient characteristics. Berke et al (2009) found that Veterans admitted to VA hospitals had longer length of stay than expected after adjustment, compared with Veterans in non-VA hospitals.…”
Section: Efficiency Of Care In Va Compared With Non-vamentioning
confidence: 99%